Comparative Analysis of HSF Genes From Secale cereale and its Triticeae Relatives Reveal Ancient and Recent Gene Expansions - Li, Xiao-Tong; Feng, Xing-Yu; Zeng, Zhen; Liu, Yang; Shao, Zhu-Qing (Frontiers in Genetics, 2021)
Plants have evolved sophisticated systems to cope with the environmental stresses, with the heat shock factor (HSF) family proteins composing an integral part of the transcriptional regulation system. Understanding the evolutionary history and functional diversity of HSFs will facilitate improving tolerance of crops to adverse environmental conditions. In this study, genome-wide analysis of the Secale cereale genome identified 31 HSF genes. The total number of HSF genes in S. cereale is larger than that in barley and the three subgenomes of wheat, suggesting it is a valuable resource for mining functional HSFs. Chromosome analysis revealed an uneven distribution of HSF genes among the 7 S. cereale chromosomes, with no HSF gene was detected on chromosome 4. Further interspecies synteny analysis revealed that chromosome reorganization during species-speciation may lead to the escape of HSF genes from the S. cereale chromosome 4. Phylogenetic analysis revealed that S. cereale experienced more HSF gene duplications than barley and the three wheat subgenomes. Expression analysis demonstrated that S. cereale HSF genes showed diverse expression patterns across plant developmental stages and upon drought and freezing treatment, suggesting functional diversity of the gene family. Notably, we detected distinct expression patterns for a recently duplicated HSF gene pair, indicating functional divergence may have occurred between the two genes. The study presents the genome organization, evolutionary features and expression patterns of the S. cereale HSF genes. These results provide new insights into the evolution of HSF genes in Triticeae and may serve as a resource for Triticeae molecular breeding.